Efficacy of Yale observation scale to detect serious bacterial infection in febrile children aged one to 36 months - Kansakar, Prerana; Shrestha, Prakash Sundar; Shrestha, Merina (Journal of Patan Academy of Health Sciences, 2015)
Introductions: In most children aged 1-36 months, the cause of a febrile illness is a self limiting viral infection. It is very difficult to distinguish these from serious bacterial infection. Objective of this study is to assess the efficacy of the Yale Observation Scale (YOS) to detect serious bacterial infection in febrile children aged 1-36 months. Methods: YOS scores were assigned as a part of a cross- sectional study in 100 children presenting in Tribhuvan University teaching hospital with fever to divide the child into well- looking if YOS ≤10 or ill- looking if YOS >10. Then the history, examination and necessary investigation was performed to come to a diagnosis of non- serious illness and serious bacterial infection. Results: Serious bacterial infection was found in 33(33%) of the patients. The sensitivity, specificity, positive and negative predictive values for a YOS score greater than 10 to detect serious bacterial infection were 45.45%, 88.05%%, 65.21% and 76.62%, respectively. Conclusions: A YOS ≤10 predicts non-serious illness while a YOS>10 does not necessarily indicate serious bacterial infection and should undergo further evaluation to confirm serious bacterial infection.